Chondrosarcoma of the Nasal Septum—A Rare Subsite: Case Report with Review of Literature - Gupta, Nidhi; Pandey, Awadhesh Kumar; Dimri, Kislay; Singhal, Surinder K; Rathee, Neeraj; Naryal, Shalu; Sharma, Pooja; Upadhyay, Amitabh Kumar (Indian Journal of Medical and Paediatric Oncology, 2021)
Chondrosarcomas are the second most common primary malignant bone tumors. Head and neck chondrosarcomas constitute less than 10% of these tumors, rarely arising from the nasal septum. These are locally aggressive malignant tumors arising from the cartilaginous framework of the nasal septum. Rarity of the tumor coupled with nonspecific symptoms makes it a diagnostic dilemma. Diagnosis requires endoscopy, radiology, and final histopathology for confirmation. Treatment is mainly surgical, requiring complete surgical excision with clear margins. Radiation has a role in unresectable tumors or for tumors with positive margins after surgery. Survival depends on the grade of tumor that predicts the metastatic potential of the tumor. We present a rare case of chondrosarcoma arising from the nasal septum in a 29-year-old young female presenting with complaints of nasal obstruction. Computed tomography was suggestive of a calcified cartilaginous tumor arising from the nasal septum. Endoscopic excision was done and postoperative histopathology showed grade II chondrosarcoma with clear margins. No adjuvant treatment was given to our patient and 2 years post-excision patient is disease free.To conclude, chondrosarcoma of the nasal septum is a rare tumor, with nonspecific symptoms. Surgery with clear margins remains the treatment of choice. Prognosis depends on the extent of tumor at presentation, resection margins, and grade of tumor.
Keywords: malignant; cartilage; head and neck; grade; treatment